Determinants of Thai Health Food Restaurant Customer Satisfaction (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Numerous factors contribute to today's consumer desire for healthy food and beverages. These include aging Asian and Western societies, urbanization, a fast-paced lifestyle, rising incomes, food safety problems, and the rise in obesity, diabetics, and other potentially harmful health problems.Thus, researchers set out to investigatehow marketing communications (MC), value recognition (VR),and customer trust (CT) contributed to Thai health food restaurants’ customer satisfaction (CS). From August 2019 to September 2019, the researchers surveyed 66 health food restaurants in Bangkok, Chiang Mai, and Khon Kaen during three service periods. Every fifth customer was randomly selected and asked to fill out the questionnaire, from which the survey achieved a 96.80% response rate (484 questionnaires). The structural equation model (SEM) analysis between variables influencing CS was conducted utilizing a latent variable LISREL 9.10path analysis and a goodness-of-fit (GOF) assessment. Results showed that the influence of the three constructs on CS was shown to be most influenced by MC (TE = 1.00), VR (TE = 0.52), and CT (TE = 0.37). Two independent variables influenced CT. These were MC (TE=0.99) and VR (TE=0.58). For VR, only the independent variableMC (TE=1.00) had an influence. Finally, the variance of the factors influencing CS (R2) was 100%, with the factors influencing CS being MC, VR, and CT, respectively.